Cost-effectiveness of a bone substitute delivering gentamicin in the treatment of chronic osteomyelitis of long bones: Protocol for the CONVICTION randomized multicenter study - Serrier, Hassan; Huot, Laure; Brosset, Sophie; Batailler, Cécile; Ferry, Tristan (Frontiers in Medicine, 2023)
Introduction: Chronic osteomyelitis is a serious osteoarticular infection that most often occurs in the long bones, responsible for significant morbidity with the risk of fracture and amputation. Despite advances in both antibiotics and surgical treatment, the probability of recurrence of infection remains at around 20%. Cerament-G (BONESUPPORT AB, Sweden) is a synthetic bone substitute that fills the bone void left by surgery, prevents infection and promotes bone regeneration within this space. Cerament-G also provides the local delivery of high doses of gentamicin over several weeks. Two prospective observational studies described a number of infectious recurrences of 4% and 5% after the use of Cerament-G. Although available in France, Cerament-G is currently not reimbursed and its high cost constitutes a barrier to its use. We hypothesize that the use of Cerament-G will lead to fewer costs to the collectivity while improving patient utility and, as an innovative strategy, will be superior to standard of care on recurrence of infection. Methods and Analysis: The Conviction Study is a prospective, multicenter, randomized, single blind study conducted in 14 French Reference Centers for Complex Osteoarticular infections. The main objective is to evaluate the cost-effectiveness of using Cerament-G in the treatment of chronic long bone osteomyelitis by comparing this innovative strategy to standard of care. A cost-utility analysis from the collective perspective will be conducted over a 24-month time horizon after the initial surgery. The outcome for the main medico-economic evaluation will be Quality Adjusted Life Years (QALYs). Discussion: The study is being conducted throughout the CRIOAc network in France, in referral centers for the management of complex infections which will facilitate patient recruitment. This study has several limitations: the investigators have to be trained to handle the device, and it was impossible to blind the surgeon. Conclusion: If the use of Cerament-G is demonstrated to be superior to leaving the dead space empty during surgery for patients with stage III chronic long bone osteomyelitis, its use will be recommended to improve the prognosis of such patients, and this device may eventually qualify for reimbursement through the French Health Insurance scheme.